Context and Oral Communication: What would be the Pedagogic Implications ? - Kamal Kumar Poudel; Hom Prasad Acharya (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Context is one of the fundamental concepts in functional linguistics. Functional linguists consider context as a pivot to linguistic analysis as well as language teaching and learning. The present study sets out to analyze data comprised by a corpus of 8000 words derived from business-situated oral Nepali (BSON). Starting with the BSON data, the study progresses through the analysis of the data in line with the guidelines permitted by grounded theory. Three themes of analysis were explored from the data: meaning, appropriacy and function. These themes were applied as the bases for further coding and categorizing the data. The most salient data  have been illustrated under five Extracts, and interpreted and discussed against the relevant literature. Consequently, it was established that natural communication occurs as a result of the interplay between linguistic forms and context of different kinds. Finally, some language-based pedagogic implications have been derived and recommended  for language teaching and learning practitioners and policy makers.